Avaliação da efetividade de um conjunto de medidas multidimensionais para prevenção de pneumonia associada à ventilação mecânica em unidade de terapia intensiva - Souza, Geovania Maciel de (2019)
Introduction: Infections related to health care are seen as care nonconformities, with impact on morbidity and mortality indicators and hospital costs. Ventilator-Associated Pneumonia (VAP) is one of the most important complications within the Intensive Care Unit (ICU), composing 85% of registered pneumonia. In order to reduce VAP rates, the national patient safety policy has been guiding the implementation of a set of low financial cost measures, that when per-formed jointly and continuously, they have a high impact safety and quality results. This set of activities is known as a bundle or care package. Objectives: To evaluate the effectiveness of a set of multidimensional measures for the prevention of VAP, including the knowledge of pro-fessionals and their adherence to prevention items. Method: Retrospective cohort study that used secondary data from the service and cross-sectional study that evaluated data from the intervention in an intensive care unit of a university hospital, during the years 2017 and 2018. The study consists of two sections: 1) knowledge of VAP indicators and patient profile admitted to the study unit before and after the implementation of multidimensional VAP prevention strat-egies; 2) identification of knowledge and adherence rate of ICU professionals on preventive measures for VAP. Results: In 2017, 14 cases of VAP were reported; in 2018, eight, with a 42,6% reduction in rates. There was no statistical significance between the patients admitted in 2017 and 2018. The median age ranged from 63 (2017) to 60 (2018), with no difference in the number of days of MV and clinical outcome. Regarding the knowledge of professionals about the prevention of VAP, 52 professionals were evaluated, and the proportion of correct answers ranged from 53% to 98.07%. Compliance with VAP prevention activity records ranged from zero to 79%. Keeping the headboard elevated as a way to prevent VAP was associated with a decrease in VAP in 2017 (p = 0.046). Oral hygiene was significant for the prevention of VAP in the sum of the two years (p = 0.019). Conclusion: There was reduction in VAP rates after the implementation of the multidimensional preventive measures package. The team's knowledge about VAP prevention proved to be widespread among the various professional categories. Ad-herence to the prevention items for VAP presented rates below ideal for the maintenance of safe and quality care. An in-service education program would be a strategy for maintaining improvements and better adherence to VAP prevention activities.